10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
This study evaluated the mediating effects of smoking and functional disability on the association between loneliness and mortality. This multinational cohort study harmonized longitudinal data from eight databases, including the UK Biobank, comprising 685,134 participants aged 40 years and older across three continents. Results revealed that loneliness was associated with increased all-cause mortality directly, and indirectly through smoking and functional disability. These findings highlight the imperative need for customized interventions focused on reducing smoking and mitigating functional disability to alleviate the detrimental impact of loneliness on mortality.